Genetic analysis of diabetes and insulitis in an interspecific cross of the nonobese diabetic mouse with Mus spretus. - de Gouyon, B (1993)
The nonobese diabetic (NOD) mouse is a widely used model for genetic studies of insulin-dependent diabetes mellitus due to the similarities between the murine and human diseases. To aid in the localization and identification of diabetes-related susceptibility genes, we have constructed an interspecific backcross between NOD and Mus spretus (SEG/Pas) mice. Although no diabetic animals were observed in the first backcross generation of (SEG/Pas x NOD) x NOD (BC1), the incidence of insulitis (lymphocyte infiltration of the islets of Langerhans) exceeded 20% after injections of cyclophosphamide, a treatment that provokes an acute form of diabetes in NOD mice. Insulitis, a prediabetic condition, is a useful phenotype in studies of diabetes susceptibility. In the second backcross (BC2) generation, 8% of the animals became diabetic and 76% were found to have insulitis. Genetic mapping studies in the BC2 families confirmed the importance of the major histocompatibility complex region on the severity of insulitis and suggested that additional susceptibility loci were linked to markers on mouse chromosomes 3, 6, and 15. Mus spretus crosses have been an important tool in recent advances in murine genetics, and our results extend their usefulness to the study of a multifactorial disease.